Time‐resolved dosimetry using a pinpoint ionization chamber as quality assurance for IMRT and VMAT a). Issue 4 (17th March 2015) - Louwe, Robert J. W.; Wendling, Markus; Monshouwer, René; Satherley, Thomas; Day, Rebecca A.; Greig, Lynne
Abstract : Purpose: To develop a method to verify the dose delivery in relation to the individual control points of intensity modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT) using an ionization chamber. In addition to more effective problem solving during patient‐specific quality assurance (QA), the aim is to eventually map out the limitations in the treatment chain and enable a targeted improvement of the treatment technique in an efficient way. Methods: Pretreatment verification was carried out for 255 treatment plans that included a broad range of treatment indications in two departments using the equipment of different vendors. In‐house developed software was used to enable calculation of the dose delivery for the individual beamlets in the treatment planning system (TPS), for data acquisition, and for analysis of the data. The observed deviations were related to various delivery and measurement parameters such as gantry angle, field size, and the position of the detector with respect to the field edge to distinguish between error sources. Results: The average deviation of the integral fraction dose during pretreatment verification of the planning target volume dose was −2.1% ± 2.2% (1 SD), −1.7% ± 1.7% (1 SD), and 0.0% ± 1.3% (1 SD) for IMRT at the Radboud University Medical Center (RUMC), VMAT (RUMC), and VMAT at the Wellington Blood and Cancer Centre, respectively. Verification of the dose to organs at risk gave very similar results but was generally subject to a larger measurement uncertainty due to the position of the detector at a high dose gradient. The observed deviations could be related to limitations of the TPS beam models, attenuation of the treatment couch, as well as measurement errors. The apparent systematic error of about −2% in the average deviation of the integral fraction dose in the RUMC results could be explained by the limitations of the TPS beam model in the calculation of the beam penumbra. Conclusions: This study showed that time‐resolved dosimetry using an ionization chamber is feasible and can be largely automated which limits the required additional time compared to integrated dose measurements. It provides a unique QA method which enables identification and quantification of the contribution of various error sources during IMRT and VMAT delivery.